Investigating washback effects of 10-11th grades English test. (Journal of Educational Sciences, 2023)
This research work contained the investigating washback effects in English lessons for secondary school students at one of the Turkestan region's village.  Since correct using of test affects the quality of educational process, in our research we focused on discussing test for the proper development of washback.  In writing the article, there was used the works of foreign and Kazakh scientists on this topic.The purpose of this research was to determine the effectiveness of using tests in the classrooms. This research paper focuses on the impact of the washback in language learning and teaching and the students’ attitudes towards the effectiveness of taking tests in terms of reflecting students’ English proficiency levels.For this survey was used quantitative method of data to analyze the thoughts of pupils about the test in order to identify washback impact of language learning in the classroom. The quantitative data was analyzed through the Statistical Package for Social Sciences Program (SPSS 23.0). The data collected from the school M. Auezov which is situated in village Orangai in Turkestan region. They were 10-11th grades pupils. The survey involved 73 students. The study was conducted in the first term of 2022-2023 academic years. The result of the study showed that there weren’t any differences between genders in some participants’ survey scale. The mostly students agreed that washback gives them the opportunity take high quality in the UNT and take high score.       Key words: washback, impact, language learning, test, assessment.